An Ability of Translating Covid-19 Related Article of English Department Student on Teaching and Education Faculty - Feby Meuthia Yusuf; Amalya Widya Sari (Jurnal Ilmiah Pendidikan Scholastic, 2022)
This research is motiyated by the difficulties of students in translating article related COVID-19 from English into Bahasa Indonesia. The purpose of this study was determine by the ability of students in translating article. The method used in this research was descriptive gualitative method. In this research, the member of the population member was 14 students, the population was the students from English department 15"-17" academic year of Universitas Ekasakti. The sample of this research was total sampling. Instrument that use in this research was translating an article related COVID-19. This data obtained from the result of test given to students, the authors found the value of three criteria of translating skill in article COVID-19, 'Accuracy, Grammatically and Eguivalence, It can be coneluded that the ability of students Accuracy is high, obtained 13 from 14 students got high score (92.86) and Grammatically there are 13 from 14 students got high score (92.890) and Eguivalence there are 13 from 14 students got high score (92.896). Based in the research analysis, the researcher was suggested to Translation lecturer give students more task and practice their translation skill. Thus, the students are trained in translating,